1976
DOI: 10.1172/jci108337
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the structural abnormality of fibrinogen Paris I.

Abstract: A B S T R A C T The structural properties of an inherited fibrinogen abnormality designated fibrinogen Paris I were investigated. Dodecyl sulfate gel electrophoresis of unreduced samples revealed no discernible differences in molecular weight from normal; this implied that in fibrinogen Paris I, the normal fibrinogen architecture of six covalently linked chains per molecule is preserved. Examination of dithiothreitol reduced samples before and after treatment with Reptilase or thrombin revealed that the Aa-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 42 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Crosslinking of fibrin was carried out under the following conditions: fibrinogen, 0.5-3 mg/ml; cysteine-HCI (adjusted to pH 7.4 with Tris), 7-10 mM; Ca2 , [15][16][17][18][19][20][21][22][23][24][25] (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinking of fibrin was carried out under the following conditions: fibrinogen, 0.5-3 mg/ml; cysteine-HCI (adjusted to pH 7.4 with Tris), 7-10 mM; Ca2 , [15][16][17][18][19][20][21][22][23][24][25] (15,16).…”
mentioning
confidence: 99%
“…However, close inspection indicated that the peak 2 -y chain position band usually was somewhat broader than that of peak 1. By varying the conditions of electrophoresis (e.g., 10% acrylamide, 4 mA per gel, 16 hr; see gels 9 and 10), the relative broadness of the peak 2 y chain band could be more easily appreciated. Occasionally, it even could be resolved into two bands, although sharp definition was never obtained.…”
mentioning
confidence: 99%
“…Fibrinogen Paris I is structurally characterized by the insertion of 15 amino acids after ␥ Q350, and functionally manifests as a polymerization defect with normal cross-linking of the wild-type ␥ chains and no cross-linking of the ␥ Paris I chains. 35 Analysis of the clot by electron microscopy also reveals abnormal clumps with irregular fibers and frequent terminations. 36 Consistent with such conclusions is the low turbidity at high-salt concentration (Table 1), which has a characteristic effect on lateral aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…In fibrinogens Bethesda III [17], Baltimore I [18], Paris II [19], Nancy [20] and Philadelphia [2], the abnormality lies in the elution of the first peak, whereas in Paris I [22], the two fibrinogen peaks emerged later than their presumed counterparts.…”
Section: Discussionmentioning
confidence: 99%